2014
DOI: 10.3991/ijet.v9i3.3308
|View full text |Cite
|
Sign up to set email alerts
|

Multimedia Based E-learning : Design and Integration of Multimedia Content in E-learning

Abstract: Abstract-The advancement in multimedia and information technologies also have impacted the way of imparting education. This advancement has led to rapid use of e learning systems and has enabled greater integration of multimedia content into e learning systems. This paper present a model for development of e learning systems based on multimedia content. The model is called "Multimedia based e learning" and is loosely based on waterfall software development model. This model consists of three distinct phases; M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 5 publications
1
16
0
3
Order By: Relevance
“…The result of previous research was reinforced through related to learning using multimedia such as Theng & Neo, namely students in Malaysia increased their performance, was more active, and motivated in learning because the lecturers used learning through multimedia by developing interactive learning modules (ILM). Meanwhile, Alshadan, et al [2] also developed a learning model by utilizing multimedia technology which also has an impact on student learning outcomes in Saudi Arabia in all disciplines and subjects.…”
Section: Introductionmentioning
confidence: 99%
“…The result of previous research was reinforced through related to learning using multimedia such as Theng & Neo, namely students in Malaysia increased their performance, was more active, and motivated in learning because the lecturers used learning through multimedia by developing interactive learning modules (ILM). Meanwhile, Alshadan, et al [2] also developed a learning model by utilizing multimedia technology which also has an impact on student learning outcomes in Saudi Arabia in all disciplines and subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Online learning facilitates the educator-learner relationship through the use of various types of ICT and electronic resources. Educators have widely regarded the use of the Internet and multimedia applications in teaching and learning activities as a vital tool for effectively delivering educational content (Alsadhan et al, 2014;Gavira and Omoteso, 2013;Perera and Richardson, 2010). Multimedia e-learning, defined as the "dissemination of material in a computer-based presentation by combining text, graphics, video, animation and sound through the Internet (Cheng and Swanson, 2011)", reflects an established method to enrich student learning.…”
Section: Introductionmentioning
confidence: 99%
“…Multimedia e-learning, defined as the "dissemination of material in a computer-based presentation by combining text, graphics, video, animation and sound through the Internet (Cheng and Swanson, 2011)", reflects an established method to enrich student learning. It has transformed conventional modes of delivering educational content such as books and written material into online, readily available interactive forms (Alsadhan et al, 2014). Wells et al (2008) also found that the use of technology in educational settings assists in the achievement of learning outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Courses are often financed by venture capital firms, nonprofit organizations, profit oriented companies, and universities (Holdaway, 2015). Alsadhan, Alhomod & Shaf (2014) express themselves less euphoric about the future potential of online courses when stating that "there is a little doubt that e-learning courses are becoming more popular each day with thousands of students joining the new courses each day. A survey of online courses reveals that most of the courses are mostly text-based."…”
Section: Introductionmentioning
confidence: 99%